Pick six eaudiobook - Monroe, Max (Mavericks Tackle Love, 2018)
Sean Phillips is a sexy as sin enigma. Cocky. Promiscuous. The New York Mavericks star wide receiver. His quick moves and sure hands extend way past the lines of the football field—and into the bedroom. Sure of himself and sure of his life, Sean's convinced he can handle anything. But when beautiful, pint-sized Six Malone delivers a challenge he's never faced before, his certainty starts to waver. Six Malone is a force to be reckoned with. Feisty. Hilarious. The popular YouCam vlogger Pick Six. The chance to work with the Mavericks on an eight-episode vlog series is the opportunity of a lifetime, and Six knows it. But after an interesting first encounter turns into a head-to-head battle with cocky football star Sean Phillips, her attention shifts—to keeping herself from falling in love. Too bad spending time with the team is part of the job, and Sean has a flawless track record . . . of getting what he wants. Pick Six: A term used when a quarterback throws an interception and a defensive player returns it for a touchdown, resulting in six points. Pick(ing) Six: When a man-wh*ring baller meets his match.